2008
DOI: 10.1097/aud.0b013e318185ddd2
|View full text |Cite
|
Sign up to set email alerts
|

Natural Boundaries in Gap Detection are Related to Categorical Perception of Stop Consonants

Abstract: A relationship between the phonetic boundary of voiced-voiceless speech sounds and the auditory temporal resolution task of detecting gaps placed within dissimilar markers, regardless of the center frequency of the trailing marker noise burst, was demonstrated. Detection of gaps between different nonspeech acoustic markers and categorical perception of VOT seems to share the same underlying perceptual timing mechanisms in native English speakers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
2
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 94 publications
(147 reference statements)
4
48
2
11
Order By: Relevance
“…Tais resultados concordam com a análise acústica realizada, pela comparação da produção do traço de sonoridade para as plosivas /b/, /d/ e /g/ entre um grupo de crianças disfônicas, com maior ocorrência de dessonorização, e um grupo de crianças sem alterações de fala 2 . Esse tipo de estudo, demonstra que, por meio de aná-lises fonético-acústicas e interpretação dos espectrogramas, relações entre os aspectos físicos e linguísticos podem ser identificadas 6,11,13 , auxiliando na compreensão da correlação entre o processo articulatório e o evento acústico resultante, e da relação entre os processos de produção e percepção da fala 10,12 . Este tipo de análise permite relacionar os distúrbios da fala, linguagem, voz e audição com os processos fisiológicos envolvidos em sua ocorrência 16 , bem como demonstrar que a criança tenha conhecimentos fonológicos não visualizáveis em sua produção motora [17][18][19] .…”
Section: Discussionunclassified
“…Tais resultados concordam com a análise acústica realizada, pela comparação da produção do traço de sonoridade para as plosivas /b/, /d/ e /g/ entre um grupo de crianças disfônicas, com maior ocorrência de dessonorização, e um grupo de crianças sem alterações de fala 2 . Esse tipo de estudo, demonstra que, por meio de aná-lises fonético-acústicas e interpretação dos espectrogramas, relações entre os aspectos físicos e linguísticos podem ser identificadas 6,11,13 , auxiliando na compreensão da correlação entre o processo articulatório e o evento acústico resultante, e da relação entre os processos de produção e percepção da fala 10,12 . Este tipo de análise permite relacionar os distúrbios da fala, linguagem, voz e audição com os processos fisiológicos envolvidos em sua ocorrência 16 , bem como demonstrar que a criança tenha conhecimentos fonológicos não visualizáveis em sua produção motora [17][18][19] .…”
Section: Discussionunclassified
“…Within-channel gap detection tasks have the inherent problem that the limiting factor may be intensity coding rather than temporal coding per se (Shailer and Moore, 1985). Compared to within-channel task, the across-channel gap detection task is more relevant to categorical perception of speech-voice onset time (VOT) perception (Elangovan and Stuart, 2008). Elangovan and Stuart (2008) showed that across-channel gap detection, but not within-channel thresholds, were related with the phonetic boundaries of voiced-voiceless speech sounds.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the perception of temporal cues that define the phonemes as voiceless or voiced depend on a well-developed skill of auditory temporal resolution (Elangovan & Stuart, 2008). This way, we could hypothesize that voiceless/voiced interchanges are a manifestation of alteration in auditory temporal processing.…”
Section: The Contribution Of Evidences On Changes In Auditory Processmentioning
confidence: 96%
“…Categorical perception can be defined (Elangovan & Stuart, 2008) as abrupt change from the perception of a phonemic category to another in a given time along a continuum. To Liberman, Harris, Hoffman and Griffith (1957) categorical perception is the degree in which the acoustic differences between variants of the same phoneme are less perceivable than the differences of the same acoustic magnitude between two different phonemes.…”
Section: Speech Perception In Dyslexic Individualsmentioning
confidence: 99%